(x+3)12=8(4x-5)

Simple and best practice solution for (x+3)12=8(4x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)12=8(4x-5) equation:


Simplifying
(x + 3) * 12 = 8(4x + -5)

Reorder the terms:
(3 + x) * 12 = 8(4x + -5)

Reorder the terms for easier multiplication:
12(3 + x) = 8(4x + -5)
(3 * 12 + x * 12) = 8(4x + -5)
(36 + 12x) = 8(4x + -5)

Reorder the terms:
36 + 12x = 8(-5 + 4x)
36 + 12x = (-5 * 8 + 4x * 8)
36 + 12x = (-40 + 32x)

Solving
36 + 12x = -40 + 32x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-32x' to each side of the equation.
36 + 12x + -32x = -40 + 32x + -32x

Combine like terms: 12x + -32x = -20x
36 + -20x = -40 + 32x + -32x

Combine like terms: 32x + -32x = 0
36 + -20x = -40 + 0
36 + -20x = -40

Add '-36' to each side of the equation.
36 + -36 + -20x = -40 + -36

Combine like terms: 36 + -36 = 0
0 + -20x = -40 + -36
-20x = -40 + -36

Combine like terms: -40 + -36 = -76
-20x = -76

Divide each side by '-20'.
x = 3.8

Simplifying
x = 3.8

See similar equations:

| 7c-9=9+7c | | 9x+13=3+9x | | 30+5y=30+5y | | x=(-10)-8 | | (4x-2)^-2/3=0 | | -4x-41=28-4x | | y=5x^2-4x-7 | | Y=ln(3x^2-4x) | | 2x^2-22=12x | | 13y+3x=110 | | 50-9.8t^2/2 | | 3x+13y=110 | | 6x+12y=8936 | | m=24-3 | | 3x^2-7=101 | | -3/7x-1/7 | | 2x+4y=422 | | Lne^4x=12 | | tan(3x+5)=4 | | x^2+12x+20=9 | | 2x^2-5=-18 | | x^2-12x-20=9 | | 7m-5-3m= | | a+2x=3-ax | | X^3-625x+300=0 | | 2/3×-3=19 | | ln(x+11)-ln(2x)=3 | | 23=x/500/17 | | 23=x/500/15 | | 5/2x=7/2x-5 | | 23=x/500/10 | | 6x^2-4=128 |

Equations solver categories